Environmental and anthropogenic gravity contributions at the Þeistareykir geothermal field, North Iceland - Forster, Florian; Güntner, Andreas; Jousset, Philippe; Reich, Marvin; Männel, Benjamin; Hinderer, Jacques; Erbas, Kemal (Geothermal Energy, 2021)
Abstract Continuous high-resolution gravimetry is increasingly used to monitor mass distribution changes in volcanic, hydrothermal or other complex geosystems. To quantify the often small target signals, gravity contributions from, e.g. atmospheric mass changes, global and local hydrology should be accounted for. We set up three iGrav superconducting gravity meters for continuous monitoring of the Þeistareykir geothermal field in North Island. Additionally, we installed a set of hydrometeorological sensors at each station for continuous observation of local pressure changes, soil moisture, snow and vertical surface displacement. We show that the contribution of these environmental parameters to the gravity signal does not exceed 10 µGal (1 µGal = 10 –8 m s −2 ), mainly resulting from vertical displacement and snow accumulation. The seasonal gravity contributions (global atmosphere, local and global hydrology) are in the order of ± 2 µGal at each station. Using the environmental observations together with standard gravity corrections for instrumental drift and tidal effects, we comprehensively reduced the iGrav time-series. The gravity residuals were compared to groundwater level changes and geothermal mass flow rates (extraction and injection) of the Þeistareykir power plant. The direct response of the groundwater levels and a time-delayed response of the gravity signal to changes in extraction and injection suggest that the geothermal system is subject to a partially confined aquifer. Our observations indicate that a sustainable “equilibrium” state of the reservoir is reached at extraction flow rates below 240 kg s −1 and injection flow rates below 160 kg s −1 . For a first-order approximation of the gravity contributions from extracted and injected masses, we applied a simplified forward gravity model. Comparison to the observed gravity ...